THU0389 Borderline pulmonary hypertension was associated with reduced cardiac output during exercise in patients with connective tissue diseases. (12th June 2018) - Marra, A.; Nagel, C.; Egenlauf, B.; Xanthouli, P.; Harutyunova, S.; Blank, N.; Lorenz, H.-M.; Fiehn, C.; Benjamin, N.; Fischer, C.; Bossone, E.; Cittadini, A.; et al.
Abstract : Background: In patients with systemic sclerosis (SSc) borderline mean pulmonary arterial pressures (mPAP; 21–24 mmHg at rest) are a frequent finding and could represent an intermediate stage between normal pulmonary pressures and manifest pulmonary hypertension (PH). 1 . Objectives: The objective of this prospective study was to compare right ventricular function and pulmonary arterial compliance (PAC) at rest and during exercise between systemic sclerosis (SSc)-patients with normal and borderline mean pulmonary artery pressures, respectively. Methods: SSc-patients (n=112) underwent clinical assessment. including right heart catheterization at rest and during exercise and were divided in three groups according to their resting mPAP values: normal mPAP (≤20 mmHg), borderline mPAP (21–24 mmHg) and manifest pulmonary hypertension (PH, mPAP ≥25 mmHg). Results were compared between groups by ANOVA followed by post-hoc student's t-test. Results: SSc Patients with borderline PAP showed significantly lower cardiac index (CI) increase during exercise and higher PVR values than SSc patients with normal PAP at rest. Six-Minute-walking distance (6MWD) and PAC (stroke volume/(systolicPAP-diastolicPAP) were significantly lower in the borderline PAP group compared to patients with normal PAP. Conclusions: The results of this study suggest that impaired 6MWD in SSc-patients with borderline PAP (and normal RV function at rest) might be caused by reduced RV contractile reserve (reduced RV output) and reduced PAC during exercise rather than by elevated pressures in the borderline range alone. These findings give further evidence for borderline PAP being an early stage of pulmonary vascular disease. Reference: [1] Visovatti SH, Distler O, Coghlan JG, Denton CP, Grünig E, Bonderman D, Müller-Ladner U, Pope JE, Vonk MC, Seibold JR, Torres-Martin JV, Doelberg M, Chadha-Boreham H, Rosenberg DM, McLaughlin VV, Khanna D. Borderline pulmonary arterial pressure in systemic sclerosis patients: a post-hoc analysis of the DETECT study. Arthritis Res Ther. 2014Dec 10;16(6):493. Acknowledgements: Special thanks to the patients that participated in this research. Disclosure of Interest: None declared